AR-Based Flashcards to Improve Primary School Students’ English Vocabulary Mastery: Insights from Vocabulary Learning Research - Rachmawati, Arandha May; Lestari, Bunga Ayu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to develop and test the effectiveness of Augmented Reality (AR) flashcards to improve English vocabulary mastery for 25 students in the fifth-grade primary school. The research method used is Research and Development (R&D) with the ADDIE development model that includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection was carried out through questionnaires, and vocabulary tests before and after treatment. The results of the study indicate that AR flashcards are very effective in supporting vocabulary learning. Validation by material experts showed a feasibility level of 93%, indicating that the content in this media is accurate, relevant, organized coherently, and appropriate to the level of cognitive development of students. Media experts also assessed AR flashcards as valid in terms of visual appearance and functionality. Teachers gave very positive responses, especially in aspects of media use and management in the classroom. Students showed high engagement, enjoyment, and increased learning motivation during learning with this media, although some experienced difficulties in understanding the language used. The test results showed a significant increase in vocabulary mastery, from 40% in the pre-cycle to 92% in the third cycle. These findings demonstrate that AR flashcards are effective and technologically innovative. The implications of this study suggest that AR flashcards can be an alternative contextual and student-centered learning medium in accordance with the Independent Curriculum. However, limitations include the limited number of subjects and the need for simplified language. Further research is recommended for broader coverage and long-term evaluation.